International Engineering Invention & Innovation Exhibition (i-ENVEX) 2011 - Anon (Universiti Malaysia Perlis, 2011)
International Engineering Invention & Innovation Exhibition (i-ENVEX) 2011 organized by Envex Young Researcher Club (EYReC), 8th - 10th April 2011 at Dewan 2020, Kangar, Perlis, Malaysia.